Global DNA methylation analysis reveals miR-214-3p contributes to cisplatin resistance in pediatric intracranial nongerminomatous malignant germ cell tumors. Issue 4 (3rd October 2017) - Hsieh, Tsung-Han; Liu, Yun-Ru; Chang, Ting-Yu; Liang, Muh-Lii; Chen, Hsin-Hung; Wang, Hsei-Wei; Yen, Yun; Wong, Tai-Tong
Abstract: Background: Pediatric central nervous system germ cell tumors (CNSGCTs) are rare and heterogeneous neoplasms, which can be divided into germinomas and nongerminomatous germ cell tumors (NGGCTs). NGGCTs are further subdivided into mature teratomas and nongerminomatous malignant GCTs (NGMGCTs). Clinical outcomes suggest that NGMGCTs have poor prognosis and survival and that they require more extensive radiotherapy and adjuvant chemotherapy. However, the mechanisms underlying this difference are still unclear. DNA methylation alteration is generally acknowledged to cause therapeutic resistance in cancers. We hypothesized that the pediatric NGMGCTs exhibit a different genome-wide DNA methylation pattern, which is involved in the mechanism of its therapeutic resistance. Methods: We performed methylation and hydroxymethylation DNA immunoprecipitation sequencing, mRNA expression microarray, and small RNA sequencing (smRNA-seq) to determine methylation-regulated genes, including microRNAs (miRNAs). Results: The expression levels of 97 genes and 8 miRNAs were correlated with promoter DNA methylation and hydroxymethylation status, such as the miR-199/-214 cluster, and treatment with DNA demethylating agent 5-aza-2ʹ-deoxycytidine elevated its expression level. Furthermore, smRNA-seq analysis showed 27 novel miRNA candidates with differential expression between germinomas and NGMGCTs. Overexpresssion of miR-214-3p in NCCIT cells leads to reduced expression of the pro-apoptotic protein BCL2-like 11 and induces cisplatin resistance. Conclusions: We interrogated the differential DNA methylation patterns between germinomas and NGMGCTs and proposed a mechanism for chemoresistance in NGMGCTs. In addition, our sequencing data provide a roadmap for further pediatric CNSGCT research and potential targets for the development of new therapeutic strategies.